Pengaruh Kohesivitas Kelompok dan Ewuh Pakewuh terhadap Pemberian Teguran Atasan Kepada Bawahan - Wibowo, Septian Angga; Ramli, Amir Hasan; Nukman, Ilhamuddin (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2016)
This research aimed to know the influence of group cohesiveness and ewuh pakewuh toward granting of reprimand supervisor to his subordinates who made faults. Ewuh pakewuh is one of Javanese culture, which is almost like an attitude or feeling embarrassed and worried if the behavior or words will offend others. The population of this research are employees from Pagottan sugar factory, Madiun, East Java who served as assistant manager or supervisor up to head division. Sampling technique used was purposive sampling technique with number of 87 subjects. Group cohesiveness, ewuh pakewuh, and granting of reprimand were measured using Likert Like scale. The analysis used multiple regression technique with F test and t test. The result showed that group cohesiveness and ewuh pakewuh jointly able to influence granting of reprimand supervisor to his subordinates (F = 17,688 and p 0,05) with RÂ² = 0,296. In addition, this research result also showed that group cohesiveness partially influence granting of reprimand supervisor to his subordinates (t = 5.904 and p 0,05), but ewuh pakewuh partially did not influence granting of reprimand supervisor to his subordinates, because t math t table and p 0,05.